Radio-frequency equipment for Uragan stellarators - Korovin, V.B.; Kramskoy, E.D. (Вопросы атомной науки и техники, 2012)
A description of high-voltage high-frequency pulse generator design is provided in the article. The matching devices and antennas that are used for plasma creating and heating, together with the ones for Uragan-2M stellarator`s chamber cleaning are also described. Приведено описание высоковольтного ВЧ-импульсного генератора, конструкций согласующих устройств и антенн, применяемых в стеллараторах «Ураган» для чистки стенок камеры, создания и нагрева плазмы. Дано опис високовольтного ВЧ-імпульсного генератора, конструкцій узгоджуючих пристроїв та антен, які застосовуються у стелараторах «Ураган» для чищення стінок камери, створення та нагріву плазми.